Do you have the tickets? - Edmondson, Brad (American Demographics, 1995)
Thirty years ago, a union card was the ticket to America's middle class, but education is the new ticket. The new, education-driven middle class is smaller, more educated, and more upscale than the factory-driven middle class of previous generations, but unfortunately the middle class is still shrinking. Males aged 25-54 who left one full-time job for another between 1990 and 1992 experienced an average earnings reduction of 20 percent. Between 1989 and 1993, median household income fell for all income groups except the highest quintile. Being able to join the middle class is the American Dream, but no one hands out tickets anymore. Today, those who want to join the middle class need to know where the good jobs will be in five years from now. If they do not, those jobs may elude them, as will the American Dream.